Kelp carbon sink potential decreases with warming due to accelerating decomposition - Filbee-Dexter, Karen; Feehan, Colette J.; Smale, Dan A.; Krumhansl, Kira A.; Augustine, Skye; Bettignies, Florian de; Burrows, Michael T.; Byrnes, Jarrett E. K.; Campbell, Jillian; Davoult, Dominique; Dunton, Kenneth H.; Franco, João N.; et al. (PLOS Biology, 2022)
Cycling of organic carbon in the ocean has the potential to mitigate or exacerbate global climate change, but major questions remain about the environmental controls on organic carbon flux in the coastal zone. Here, we used a field experiment distributed across 28° of latitude, and the entire range of 2 dominant kelp species in the northern hemisphere, to measure decomposition rates of kelp detritus on the seafloor in relation to local environmental factors. Detritus decomposition in both species were strongly related to ocean temperature and initial carbon content, with higher rates of biomass loss at lower latitudes with warmer temperatures. Our experiment showed slow overall decomposition and turnover of kelp detritus and modeling of coastal residence times at our study sites revealed that a significant portion of this production can remain intact long enough to reach deep marine sinks. The results suggest that decomposition of these kelp species could accelerate with ocean warming and that low-latitude kelp forests could experience the greatest increase in remineralization with a 9% to 42% reduced potential for transport to long-term ocean sinks under short-term (RCP4.5) and long-term (RCP8.5) warming scenarios. However, slow decomposition at high latitudes, where kelp abundance is predicted to expand, indicates potential for increasing kelp-carbon sinks in cooler (northern) regions. Our findings reveal an important latitudinal gradient in coastal ecosystem function that provides an improved capacity to predict the implications of ocean warming on carbon cycling. Broad-scale patterns in organic carbon decomposition revealed here can be used to identify hotspots of carbon sequestration potential and resolve relationships between carbon cycling processes and ocean climate at a global scale.
10 citations (Crossref) [2023-10-31]
Keywords: Carbon sequestration; Decomposition; Deep sea; Forests; Latitude; Ocean temperature; Oceans; Seaweed; dept.bio; peer-reviewed

Plant growth promotion by rhizosphere dwelling microbes - Lewis Roberts, Elizabeth (Rhizosphere Engineering, 2022)
This work summarizes the roles of various plant promoting (PGP) microorganism on several types of plant hosts. In particular, rhizosphere dwelling bacteria and fungi that increase plant growth, protect plants from pathogens, and increase tolerance to abiotic stresses are presented. These traits are due, in part, to the production of enzymes, hormones, and a plethora a various metabolites produced by rhizosphere microorganisms that directly or indirectly benefit the plants. The impact of selective grazing by bacterivorous protozoa on plant growth promotion is also examined. In addition to reviewing research from other investigators, this paper introduces a recently isolated Pseudomonad bacterium that has demonstrated growth promotion and protection of heirloom tomato (Solanum lycopersicum) in the face of both abiotic and biotic stresses. Our findings indicate that the novel Pseudomonas koreensis strain could serve as an agricultural inoculant to induce plant growth and protection. The potential to create effective bioinoculum using rhizosphere microorganisms is discussed.
Keywords: Plant growth promoting Rhizobacteria; Plant growth promoting fungi; Protozoa; dept.bio

Salted roads lead to oedema and reduced locomotor function in amphibian populations - Brady, S.P.; Goedert, D.; Frymus, L.E.; Zamora-Camacho, F.J.; Smith, P.C.; Zeiss, C.J.; Comas, M.; Abbott, T.A.; Basu, S.P.; DeAndressi, J.C.; Forgione, M.E.; Maloney, M.J.; et al. (Freshwater Biology, 2022)
Human activities have caused massive losses of natural populations across the globe. Like many groups, amphibians have experienced substantial declines worldwide, driven by environmental changes such as habitat conversion, pollution, and disease emergence. Each of these drivers is often found in close association with the presence of roads. Here we report a novel consequence of roads affecting an amphibian native to much of North America, the wood frog (Rana sylvatica). Across 38 populations distributed from southern to central New England, we found that adult wood frogs living adjacent to roads had higher incidence and severity of oedema (indicated by obvious bloating caused by subcutaneous fluid accumulation) during the breeding season than frogs living away from the influence of roads. This effect was best explained by increased conductivity of breeding ponds, probably caused by runoff pollution from road salt used for de-icing. Oedema severity was negatively correlated with locomotor performance in more northerly populations. Interestingly, northern populations experience more intense winters, which tends to result in more de-icing salt runoff and increased energetic demands associated with overwintering cryoprotection needs. Thus, this emerging consequence of roads appears to impose potential fitness costs associated with locomotion, and these effects might be most impactful on populations living in regions where de-icing is most intense. Together, our findings reveal a novel set of impacts of roads and runoff pollution on wood frog physiology and performance, which seem likely to contribute to population decline. Given the global prevalence of roads and increasing salinisation of freshwater habitats, oedema and related impacts could be widespread consequences faced by amphibian populations across much of the planet's temperate zones. © 2022 John Wiley & Sons Ltd.
1 citations (Crossref) [2023-10-31]
Keywords: amphibian; bloating; dept.bio; freshwater salinisation; peer-reviewed; performance; physiology; pollution; road salt runoff; winter de-icing

Instructional models for course-based research experience (CRE) teaching - Hanauer, D.I.; Graham, M.J.; Arnold, R.J.; Ayuk, M.A.; Balish, M.F.; Beyer, A.R.; Butela, K.A.; Byrum, C.A.; Chia, C.P.; Chung, H.-M.; Clase, K.L.; Conant, S.; et al. (CBE life sciences education, 2022)
The course-based research experience (CRE) with its documented educational benefits is increasingly being implemented in science, technology, engineering, and mathematics education. This article reports on a study that was done over a period of 3 years to explicate the instructional processes involved in teaching an undergraduate CRE. One hundred and two instructors from the established and large multi-institutional SEA-PHAGES program were surveyed for their understanding of the aims and practices of CRE teaching. This was followed by large-scale feedback sessions with the cohort of instructors at the annual SEA Faculty Meeting and subsequently with a small focus group of expert CRE instructors. Using a qualitative content analysis approach, the survey data were analyzed for the aims of inquiry instruction and pedagogical practices used to achieve these goals. The results characterize CRE inquiry teaching as involving three instructional models: 1) being a scientist and generating data; 2) teaching procedural knowledge; and 3) fostering project ownership. Each of these models is explicated and visualized in terms of the specific pedagogical practices and their relationships. The models present a complex picture of the ways in which CRE instruction is conducted on a daily basis and can inform instructors and institutions new to CRE teaching.
6 citations (Crossref) [2023-10-31] tex.document_type: Article tex.pubmed_id: 34978921 tex.source: Scopus
Keywords: Educational; Engineering; Faculty; Humans; Mathematics; Models; Students; Teaching; dept.bio; educational model; engineering; human; mathematics; peer-reviewed; student; teaching; university

Seasonal variation in the bioaccumulation of potentially toxic metals in the tissues of Astrangia poculata in the northeastern United States - Trumbauer, W.; Grace, S.P.; Rodrigues, L.J. (Marine Pollution Bulletin, 2022)
Astrangia poculata inhabits coasts near dense human populations in the northeastern United States and may be exposed to elevated pollutants. No studies have assessed heavy metal concentration in temperate corals despite their proximity to anthropogenic activity. We collected colonies four times in one year and analyzed coral tissue for As, Cd, Cr, Pb, and Zn. Most heavy metals except for As were 1.5–3.3 times lower in summer compared to other seasons. Pb, As, and Cd were three orders of magnitude higher than concentrations for other Narragansett Bay benthic species, suggesting that A. poculata bioaccumulates more readily and/or inhabits more contaminated areas of the Bay. Zn, Pb, and As had similar concentrations to tropical corals inhabiting anthropogenically polluted sites. While physiological impacts are unknown, this population of A. poculata may have a higher tolerance for heavy metal pollution than most scleractinians, making it an interesting candidate for future studies. © 2021 Elsevier Ltd
1 citations (Crossref) [2023-10-31] tex.art_number: 113180 tex.author_keywords: Astrangia poculata; Heavy metal pollution; Narragansett Bay; Seasonality; Temperate tex.coden: MPNBA tex.document_type: Article tex.pubmed_id: 34871902 tex.source: Scopus
Keywords: Animals; Anthozoa; Anthropogenic Effects; Article; Astrangia poculata; Astrangium poculatum; Bioaccumulation; Biochemistry; Chemical; Environmental Monitoring; Exposed to; Heavy; Heavy metal concentration; Heavy metals; Heavy metals pollution; Human population; Humans; Metals; Narragansett Bay; Narragansett bay; Pollution; Rhode Island; Seasonal variation; Seasonality; Seasons; Temperate; Tissue; Toxic metals; United States; Water Pollutants; animal; anthropogenic source; arsenic; benthos; bioaccumulation; cadmium; chromium; concentration (composition); concentration (parameter); coral; dept.bio; environmental monitoring; heavy metal; human; lead; metal derivative; nonhuman; peer-reviewed; pollution; season; seasonal variation; seasonality; toxic substance; water pollutant; zinc